Re-regeneration to reduce negative effects associated with tail loss in lizards - Barr, James; Boisvert, Catherine; Somaweera, R.; Trinajstic, Kate; Bateman, Bill (NATURE PUBLISHING GROUP, 2019)
© 2019, The Author(s). Many species of lizard use caudal autotomy, the ability to self-amputate a portion of their tail, regenerated over time, as an effective anti-predation mechanism. The importance of this tactic for survival depends on the degree of predation risk. There are, however, negative trade-offs to losing a tail, such as loss of further autotomy opportunities with the regenerated tail vertebrae being replaced by a continuous cartilaginous rod. The common consensus has been that once a tail has been autotomised and regenerated it can only be autotomised proximal to the last vertebral autotomy point, as the cartilage rod lacks autotomy planes. However, anecdotal evidence suggests that although the regenerated portion of the tail is unable to autotomise, it can re-regenerate following a physical shearing event. We assessed re-regeneration in three populations of the King’s skink (Egernia kingii), a large lizard endemic to south-west Western Australia and surrounding islands. We show that re-regeneration is present at an average of 17.2% across the three populations, and re-regenerated tissue can comprise up to 23.3% of an individual’s total tail length. The ability to re-regenerate may minimise the costs to an individual’s fitness associated with tail loss, efficiently restoring ecological functions of the tail.